2008
DOI: 10.1177/0731684407086506
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties of Hydroxyapatite Reinforced Poly(Methyl Methacrylate) Composites

Abstract: Poly(methyl methacrylate) (PMMA) filled with hydroxyapatite (HA) filler has been widely used in biomaterial application. Acrylic denture base material was prepared from PMMA filled with HA. This research work attempted to investigate the effects of hydroxyapatite (HA) on the flexural properties of poly(methyl methacrylate). PMMA powder was mixed with a monomer of methyl methacrylate (MMA) stabilized with hydroquinone. Benzoyl peroxide (BPO) and ethylene glycol dimethacrylate (EGDMA) were used as initiator and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 8 publications
(12 reference statements)
4
11
0
Order By: Relevance
“…Zebarjad et al [11] studied the mechanical properties of nano HA-reinforced PMMA cement were by using three point bending, compressive and wear test and concluded that there was no direct proportionality between the results of bending tests and the HA content and the addition of HA to PMMA (up to 10 wt%) did not change the bending properties significantly. Similar observation was reported by Chow Wen et al [12] who studied the flexural properties of hydroxyapatite reinforced poly(Methyl methacrylate) composites. It was found that the flexural strength and strain decreased in the presence of HA.…”
Section: Introductionsupporting
confidence: 87%
“…Zebarjad et al [11] studied the mechanical properties of nano HA-reinforced PMMA cement were by using three point bending, compressive and wear test and concluded that there was no direct proportionality between the results of bending tests and the HA content and the addition of HA to PMMA (up to 10 wt%) did not change the bending properties significantly. Similar observation was reported by Chow Wen et al [12] who studied the flexural properties of hydroxyapatite reinforced poly(Methyl methacrylate) composites. It was found that the flexural strength and strain decreased in the presence of HA.…”
Section: Introductionsupporting
confidence: 87%
“…It is interesting to note that the degree of crystallinity of PBT increased in the presence of OMMT. This is attributed to the nucleation effects of OMMT resulting in the improvement, in the crystal perfection of PBT 79 . A similar observation was reported by Mohd Ishak et al, for the injection moulded short glass fiber reinforced PBT composites 80 .…”
Section: 1 Effect Of Loading Clay With Pbt-pc 80-20 Blendmentioning
confidence: 99%
“…Whereas, when adding12% Pistachio Shell powder of average particle size of about (150µm) to PMMA led to increasing in Tg value of PMMA composites to 123.8℃ as shown in figure (9). Furthermore, the DSC scans of PMMA composite specimens were reinforced with Pistachio Shell powder of different average particle size in the PMMA matrix showed an increase of (Tg), due to the nature of natural powders (Pistachio Shell), which is acting as an agent caused restriction and limited in the PMMA chain mobility, Finally, that leads to increase the molten state viscosity and rise the glass transition temperature for all composite specimens, [Carola Esposito Corcione 2012, Chow Wen Shyang. et.…”
Section: Dsc Testmentioning
confidence: 99%